Biosynthesis and molecular genetics of fungal secondary metabolites - Garcia-Estrada, Carlos; Zeilinger, Susanne; Martin, Juan-Francisco (Fungal Biology, 2014)
This volume describes the more relevant secondary metabolites of different fungi with current information on their biosynthesis and molecular genetics. Bolstered with color illustrations and photographs, the book describes the possible application of molecular genetics to directed strain improvement in great detail. The needs for future developments in this field are also discussed at length.   Written by authorities in the field, Biosynthesis and Molecular Genetics of Fungal Secondary Metabolites provides a cutting-edge perspective on fungal secondary metabolism and underlying genetics and is a valuable resource for scientists, researchers, and educators in the field of fungal biology.